The relationship between the Italian nationallegal system and EU law, and the roleof the Italian Constitution Court - Mangione, Gabriella (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Italy was one of the countries that signed the Treaty of Rome in 1957, which created the European Economic Community.Despite initial resistance and the numerous difficulties encountered during subsequent years, the choice to commit to Europe was widely shared, becoming irreversibly embedded in the national consciousness.However, whilst other legal systems chose at various stages of their European journey to amend their constitutions by incorporating a European clause, this never happened in Italy. Italy did not change its Constitution as a result of joining the European Economic Community, and has not done so subsequently after becoming part of the European Union with the Maastricht Treaty, following the adoption of the Treaty of Lisbon, nor indeed at any subsequent stage in the process of European integration.It was only in 2001, with the reform of Title V of the Constitution involving changes in the allocation of powers between the state, the regions and the local authorities, that the expression "Community law" was incorporated into the Constitution.
Keywords: Włoski Trybunał Konstytucyjny; Europa; klauzula europejska; Italian Constitutional Court; Europe; constitution